The Experience of Retirement in Britain, Past and Present - Thane, Pat (Österreichische Zeitschrift für Geschichtswissenschaften, 2011)
Until quite recently in Britain retirement was possible only for the better-off. Most poorer people, until the mid-twentieth century, worked for survival until they dropped. The rich could always retire when they chose, most others only when required by their occupation or pension scheme. In Britain, externally imposed retirement, with a pension, began in the 19th century in the public service, then spread to cover the whole working population after World War 2, often as a management strategy supposed to improve efficiency. When male manual workers were first obliged to retire they found the sudden transition in their lives an unwelcome shock. Women found it easier because domestic work continued and they generally had closer family and friendship networks to sustain them. Later generations, by the 1960s and 70s learned to look forward to a period of leisure in later life though for many, especially women, it was a life of poverty. But older people were healthier than in the past and often active in voluntary work, caring for grandchildren and others. Retirement ages fell in 1980s and 1990s, then rose again under pressure from government and employers concerned about declining numbers of younger workers and the costs of pensions to growing numbers of older people.